Gender Differences in Characteristics of Adolescents Presenting to the Emergency Department with Acute Assault-Related Injury - Ranney, Megan L. (2011)
OBJECTIVES: Adolescents with a history of peer assault are known to report high rates of other risky behaviors. The characteristics of adolescents seeking care in the ED for acute assault-related injury are less well-established. This knowledge deficit is particularly noticeable for adolescent female victims of peer assault. This study’s objectives were: 1) to characterize the demographics and risk behaviors of youths presenting to the emergency department (ED) with acute assault-related injury; and 2) to compare assaulted youths’ demographic characteristics, past experiences with violence, and other risk behaviors by sex. METHODS: A systematic sample of adolescents (ages 14 to 18 years) presenting to an urban ED with acute assault-related injury (excluding dating violence, sexual assault, and child abuse) was recruited. Consenting participants self-administered a computerized survey about demographics, history of peer and dating aggression, and theoretical correlates of violence (e.g., alcohol and other drug use, depressive symptoms, weapon carriage). Multivariate logistic regression was performed to identify factors that were differentially associated with presentation to the ED for acute assault-related injury for females versus males. RESULTS: Of 3,338 adolescents completing a screening survey during the 36-month study period, 197 had presented to the ED with acute assault-related injuries; seven of these were excluded from this study due to being victims of dating violence. Most (n = 179, 94.2%) of these 190 acutely assaulted participants were discharged home. The majority reported a history of past-year peer aggression (n = 160, 84.2%) and past-year violent injury (n = 106, 55.8%). Similar rates of past-year peer aggression, past-year violent injury, alcohol use, and weapon carriage were observed for adolescent males and females presenting with acute assault-related injury. Males and females also reported similar age, race, socioeconomic status, and education levels. As compared to males, females were less likely to report living with a parent (OR 0.25, 95% CI = 0.08 to 0.84), and were more likely to report depressive symptoms (OR 2.59, 95% CI = 1.23 to 5.48) and past-year dating aggression (OR 2.23, 95% CI = 1.04 to 4.82). CONCLUSIONS: Male and female adolescents with acute assault-related injuries were very similar. Both reported extremely high rates of past year peer violence, assault-related injury, and substance use. The greater prevalence of some risk factors among adolescent females, such as depressive symptoms, dating aggression, and independent living status, should be further investigated.